Household income implications of improved fertilizer accessibility and lower use inefficiency: Long-term scenarios for Ethiopia - Ermias Engida Legesse; Amit Kumar Srivastava; Arnim Kuhn; Thomas Gaiser (University of Bonn, Center for Development Research (ZEF), 2019)
High population growth rates in Ethiopia are likely to aggravate farmland scarcity, as the agrarian share of the population stays persistently high, but also create increasing demand for food and non-food biomass. Based on this expectation, this study investigates welfare implications of interventions that improve access and knowhow to modern farming inputs in order to improve crop biomass productivity. Using a dynamic meso-economic modeling framework for Ethiopia, ex-ante scenarios that simulate a) decreased costs of fertilizer use for all crops and b) elevated efficiency of fertilizer application for wheat and maize are run for a period of 20 years. These interventions together lead to yield increases of 4 percent for wheat and 12.5 for maize on average across simulation years as compared to the base run. The increased fertilizer application is also found to be profitable for the average farmer despite the price reductions for wheat and maize due to increased market supply. As a result of price and income effects of the interventions, all household types exhibit welfare gains. Non-farming households, being net consumers, enjoy lower costs of living due to lower commodity prices. Rural farming households enjoy even higher welfare gains as non-farming households because they exhibit higher consumption shares of the two food commodities in question, and because their farming profits increase.
Keywords: 330; CGE; fertilizer-yield-response; productivity; welfare; Ethiopia